Left coronary artery calcification patterns after coronary bypass graft surgery: An in‐vivo optical coherence tomography study. Issue 3 (11th September 2020) - Wolny, Rafal; Mintz, Gary S.; Matsumura, Mitsuaki; Kim, Song‐Yi; Ishida, Masaru; Fujino, Akiko; Lee, Tetsumin; Shlofmitz, Evan; Goldberg, Alec; Liu, Yangbo; Zhang, Zixuan; Zhang, Mingyou; et al.
Abstract: Objectives: We sought to evaluate the severity and patterns of calcifications in the left main coronary artery (LMCA) and proximal segments of left anterior descending coronary artery (LAD) and left circumflex artery (LCX) using optical coherence tomography (OCT) in patients with and without prior coronary artery bypass grafting (CABG). Background: CABG may accelerate upstream calcium development. Methods: OCT images ( n  = 76) of the LMCA bifurcation from either the LAD or LCX in 76 patients with at least one patent left coronary graft, on average 7.0 ± 5.6 years post‐CABG, were compared with 148 OCT images in propensity‐score‐matched non‐CABG controls. RESULTS: Minimum lumen areas in the LMCA, LAD, and LCX in post‐CABG patients were smaller than non‐CABG controls. Maximum calcium arc and thickness as well as calcium length were greater in the LMCA and LCX, but not in the LAD in post‐CABG patients versus non‐CABG controls. Calcium located at the carina of a bifurcation, calcified nodules (CN), thin intimal calcium, and lobulated calcium were more prevalent in post‐CABG patients. After adjusting for multiple covariates, prior CABG was an independent predictor of calcification at the carina of a bifurcation (odds ratio [OR] 5.77 [95% confidence interval, CI: 1.5–21.6]), thin intimal calcium (4.7 [1.5–14.4]), and the presence of a CN (15.60 [3.2–76.2]). Conclusions: Prior CABG is associated with greater amount of calcium in the LMCA and the proximal LCX, as well as higher prevalence of atypical calcium patterns, including CN, thin or lobulated calcium, and calcifications located at the carina of a bifurcation, compared with non‐CABG controls.